COLLABORATION OF PANCASILA STUDENT PROFILE STRENGTHENING PROJECT INTEGRATED WITH ISLAMIC PERSONAL DEVELOPMENT ACTIVITIES IN SHAPING STUDENT CHARACTER AT SDIT AL-FURQON PALEMBANG - Dian, Nyayu; Astuti, Mardiah; Oviyanti, Fitri (Jurnal Konseling Pendidikan Islam, 2025)
This study evaluates the integrated Pancasila Student Profile Project (P5) and Islamic Personal Development (BPI) at SDIT Al-Furqon Palembang as a whole-school character strategy. A qualitative field design combined observation, interviews, and document review; data were analyzed with Miles Huberman procedures and Edwards’ implementation factors. P5 operated co-curricularly (Entrepreneurship & Sustainable Lifestyle themes; 8 periods on Fridays) through an introduction, contextualization, action reflection follow-up sequence; BPI ran routinely via character mentoring, Friday Muhasabah, and a Night Study Club. A four-level rubric integrated formative and summative evidence. Findings show gains in ethics toward nature/others, discipline and responsibility, collaboration, creativity/innovation, critical reasoning, and religious conduct. Enablers included strong communication, adequate human/material resources, positive leadership, clear SOPs/KOSP, parent partnerships, and up-front budgeting; time and initial reference gaps were the main constraints. The P5 BPI model is effective and sustainable; recommended next steps are stronger formative coaching, teacher PD in project design/assessment, formalized parent/community roles, and digitized portfolios.